SARS-CoV-2 Spike Protein S1-Mediated Endothelial Injury and Pro-Inflammatory State Is Amplified by Dihydrotestosterone and Prevented by Mineralocorticoid Antagonism - Kumar, Nitin; Zuo, Yu; Yalavarthi, Srilakshmi; Hunker, Kristina L.; Knight, Jason S.; Kanthi, Yogendra; Obi, Andrea T.; Ganesh, Santhi K. (Viruses, 2021)
Men are disproportionately affected by the coronavirus disease-2019 (COVID-19), and face higher odds of severe illness and death compared to women. The vascular effects of androgen signaling and inflammatory cytokines in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-mediated endothelial injury are not defined. We determined the effects of SARS-CoV-2 spike protein-mediated endothelial injury under conditions of exposure to androgen dihydrotestosterone (DHT) and tumor necrosis factor-a (TNF-α) and tested potentially therapeutic effects of mineralocorticoid receptor antagonism by spironolactone. Circulating endothelial injury markers VCAM-1 and E-selectin were measured in men and women diagnosed with COVID-19. Exposure of endothelial cells (ECs) in vitro to DHT exacerbated spike protein S1-mediated endothelial injury transcripts for the cell adhesion molecules E-selectin, VCAM-1 and ICAM-1 and anti-fibrinolytic PAI-1 (p < 0.05), and increased THP-1 monocyte adhesion to ECs (p = 0.032). Spironolactone dramatically reduced DHT+S1-induced endothelial activation. TNF-α exacerbated S1-induced EC activation, which was abrogated by pretreatment with spironolactone. Analysis from patients hospitalized with COVID-19 showed concordant higher circulating VCAM-1 and E-Selectin levels in men, compared to women. A beneficial effect of the FDA-approved drug spironolactone was observed on endothelial cells in vitro, supporting a rationale for further evaluation of mineralocorticoid antagonism as an adjunct treatment in COVID-19.